Cerebral consequences of environmental noise exposure. (July 2022) - Hahad, Omar; Bayo Jimenez, Maria Teresa; Kuntic, Marin; Frenis, Katie; Steven, Sebastian; Daiber, Andreas; Münzel, Thomas
Abstract: The importance of noise exposure as a major environmental determinant of public health is being increasingly recognized. While in recent years a large body evidence has emerged linking environmental noise exposure mainly to cardiovascular disease, much less is known concerning the adverse health effects of noise on the brain and associated neuropsychiatric outcomes. Despite being a relatively new area of investigation, indeed, mounting research and conclusive evidence demonstrate that exposure to noise, primarily from traffic sources, may affect the central nervous system and brain, thereby contributing to an increased risk of neuropsychiatric disorders such as stroke, dementia and cognitive decline, neurodevelopmental disorders, depression, and anxiety disorder. On a mechanistic level, a significant number of studies suggest the involvement of reactive oxygen species/oxidative stress and inflammatory pathways, among others, to fundamentally drive the adverse brain health effects of noise exposure. This in-depth review on the cerebral consequences of environmental noise exposure aims to contribute to the associated research needs by evaluating current findings from human and animal studies. From a public health perspective, these findings may also help to reinforce efforts promoting adequate mitigation strategies and preventive measures to lower the societal consequences of unhealthy environments.